Self Care Profile of Diabetic Patient during Covid 19 Pandemic in Manggarai Regency, East Nusa Tenggara - Lidwina Dewiyanti Wea; Maria Getrida Simonb; Aldegonda F.Jeharutc; Rosalia Padutd; Viktoria K.Danue; V.C Agnes Bataf (Journal of Ners and Midwifery, 2021)
Diabetes mellitus (DM) is one of the comorbid diseases commonly found on COVID-19 infected individuals and causing the most death. In the pandemic era, DM patients are needful to execute the care management by themselves due to the social restriction as a part of transmission control. This study aimed to assess the self-care behavior of DM patients during the COVID-19 pandemic era in Manggarai Regency who still carry out various traditional ceremonies even during the pandemic. This study was a quantitative descriptive study. The research data get by the SDSCA (The Summary of Self-Care Activities) questionnaire developed by the General Service Administration (GSA) Regulatory Information Service Center (RISC). This study attends from January to March 2021, with 88 respondents have participated after being recruited using purposive sampling and inclusion criteria. Among the 88 respondents, the respondents were most compliant with eating restrictions on sugar-contained food such as cake, chocolate, biscuit, and ice cream diet. Respondents did not restrict themself to consume carbohydrate contained foods. Self-care behavior is most important to DM patients in the pandemic era due to the social restrictions creating the hesitancy among the patients to come to the health care facilities. Moreover, when DM patients are more prone to develop severe symptoms of covid-19. Health professionals have to improve the health education to the patients by emphasizing the importance of exercise, diabetic foot care, and routine blood sugar monitoring so that the patients are not only focused on dietary management and medicine.